Corrosion inhibition of powder metallurgy Mg by fluoride treatments - Pereda, María Dolores (2010)
Pure Mg has been proposed as a potential degradable biomaterial to avoid both the disadvantages of nondegradable internal fixation implants and the use of alloying elements that may be toxic. However, it shows excessively high corrosion rate and insufficient yield strength. The effects of reinforcing Mg by a powder metallurgy (PM) route and the application of biocompatible corrosion inhibitors (immersion in 0.1 and 1 M KF solution treatments, 0.1 M FST and 1 M FST, respectively) were analyzed in order to improve Mg mechanical and corrosion resistance, respectively. Open circuit potential measurements, polarization techniques (PT), scanning electrochemical microscopy (SECM) and electrochemical impedance spectroscopy (EIS) were performed to evaluate its corrosion behavior. SECM showed that the local current of attacked areas decreased during the F treatments. The corrosion inhibitory action of 0.1 M FST and 1 M FST in phosphate buffered solution was assessed by PT and EIS. Under the experimental conditions assayed, 0.1 M FST revealed better performance. X-ray photoelectron spectroscopy, energy dispersive X-ray and X-ray diffraction analyses of Mg(PM) with 0.1 M FST showed the presence of KMgF3 crystals on the surface while a MgF2 film was detected for 1 M FST. After fluoride inhibition treatments, promising results were observed for Mg(PM) as degradable metallic biomaterial due to its higher yield strength and lower initial corrosion rate than untreated Mg, as well as a progressive loss of the protective characteristics of the F-containing film which ensures the gradual degradation process.